Kajian Hukum Perbuatan Phisycal Abuse Bagi Anak (Persfektif UU No. 35 Tahun 2014 Tentang Perlindungan Anak) - Yusuf hanafi, Yusuf Hanafi (DOKTRINA: JOURNAL OF LAW, 2025)
The research aims to discuss the regulation of physical abuse in criminal law and the categories of acts that fall into physical abuse for children and criminal sanctions against perpetrators who commit physical abuse for children from the perspective of child protection laws. The research method used is a type of normative legal research, referring to secondary data sourced from library data. The results obtained are the regulation of physical abuse in criminal law as regulated by Law No. 35 of 2014 concerning Amendments to Law No. 23 of 2002 concerning Child Protection, namely in Article 1 paragraph 15A and Article 76C which reads "everyone is prohibited from placing, allowing, doing, ordering, or participating in committing violence against children. Categories of acts that fall into physical abuse for children Acts of violence can also result in victims suffering injuries ranging from minor injuries to serious injuries or even causing the victim to die. Criminal sanctions against perpetrators who commit acts of physical abuse against children from the perspective of the Child Protection Law, namely the threat of criminal penalties, have been regulated in Article 80 of the Child Protection Law, the threat of criminal penalties ranging from 3 years to 15 years in prison.